Analysis of Factors Affecting Patients' Quality of Life Type 2 Diabetes Mellitus in Puskesmas Sudiang Raya Makassar City - Zulfiah Zulfiah; Yuniharce Kadang; Herlina Klarista Mina (Politeknik Sandi Karsa, 2021)
Diabetes Mellitus Type 2 is a metabolic disorder characterized by increased levels of sugar in the blood (hyperglycemia) due to the disorder. Diabetes can affect the quality of life with several aspects, namely diabetes care, symptoms of diabetes, and chronic complications that cause high morbidity and mortality rates for people with type 2 diabetes, which reduces the quality of life for people with type 2 diabetes. The purpose of this study was to analyze the factors that influence the quality of life of type 2 DM patients at the Sudiang Raya Public Health Center Makassar in 2021. The research method used was cross sectional method. The population consisted of 120 patient diagnosed with Diabetes Mellitus type 2. By total sampling method, 120 respondents were chosen. The data were analyzed by using univariate analysis by gaining frequency of data, bivariate analysis using chi-square and multivariate analysis using regression linear. Factors analyzed were, family support. The result show that significant factors affecting the quality of life in patient with diabetes mellitus type 2 are family support (p value=0,005).